European identity – a lot of water will pass - Šuvaković, Uroš V. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The basic problem that the process of Euro integrations faces today is the absence of the European identity. There are ideas how it could be built, on what it should be based, but the basic problem is the EU has give up in a great extent from the real European values – the ideals like freedom, equality, solidarity, social justice, etc. Human rights are the European achievement, but a distinctive, therefore identity difference between the European and the Anglo-American interpretation is that the European variant guaranteed social-economic rights, which was actually a concretization of the great ideal of solidarity. Today, with prevailing ideology of globalism, just this element of human rights has been brutally waded, a part of the European identity with it. A similar situation is with what the Europeans consider the greatest achievement of the EU – free movement of people, goods and capital. Free movement of people is questioned by building barbed wires and creation of a new аntemurale сhristianitatis, even in Islamic states, far away from the Schengen Area that is proclaimed untouchable. Moreover, all those people swarming to the Europe actually have close connections with it – they originate from former European colonies, brutally exploited by their metropolises for decades and centuries. Not only that, but recently their new “Europeanization” has been attempted through the initialization of the “Arab Spring”, which resulted with increase of the Islamic fundamentalism, disintegration of certain Arab states and tribal war in them, increase of terrorism and, of course, migrants from those areas. Although it would be justified to try to return the evil gotten to them at least partly, by refusing to accept the miserable the Europe gives the mortal strike to some of the main values that are considered its identity characteristics – free movement of people and solidarity. All this, actually, indicates on the absence of the European identity consciousness. There is no clearly defined content of the idea of the Euroidentity, nor there is consciousness of it with the citizens of the EU. The citizens of the EU are still more French, Englishmen, Germans, Italians, Spaniards, Poles, Czechs rather than the Europeans. Their Europeanism exists only on the level of usefulness and efficacy, therefore, the prediction is that the model of the EU as an international organizationsui generiswill be kept for a long time, while identities in future will be tied for (European) nations.